Building a high-performance organic cathode material containing electron-withdrawing groups for lithium-ion batteries. (1st August 2023) - Shen, Daozhen; Chen, Xiaojuan; Chen, Chen; Yang, Baozhu; Jiang, Qingyan; Su, Lixin; Zhang, Hanping; Liu, Hong-Jiang; Liu, Qi
Abstract: The capacity of cathode materials is one of the main factors to limit the performance of lithium-ion batteries (LIBs), so it is urgent to develop high-performance cathode materials. Herein, trinitrohexaazatrinaphythylene (TNHATN) including an electron-withdrawing group (nitro, -NO2 ) was synthesized by the condensation reaction between hexaketocyclohexane and 4-nitro- o -phenylenediamine, and it was first investigated as a cathode material for lithium-ion batteries. The TNHATN electrode displays a high discharge specific capacity of 355.7 mAh g −1 at 0.05 A g −1 and a superior cycling stability, having the capacity retention of 97.9 % after 200 cycles. The excellent behaviors may be ascribed to its π-conjugated structure including electron-withdrawing groups and multiple redox active sites. The experimental results reveal the redox active sites are pyrazine nitrogen atoms and oxygen atoms from nitro groups. This work confirms that it is an effective route to introduce an electron-withdrawing group into a π-conjugated compound for obtaining high-performance organic cathode materials of LIBs. Highlights: Trinitrohexaazatrinaphythylene (TNHATN) was synthesized. TNHATN can be used as cathode materials for Li-ion batteries. TNHATN electrode presents a high discharge capacity and a superior cycling stability. TNHATN molecule has multiple redox active sites.